10,000 days of thunder : a history of the Vietnam War - Caputo, Philip (Atheneum Books for Young Readers, 2005)
Presents a collection of illustrated photographs and maps depicting the war in Vietnam from its beginning under French control to the fall of Saigon in 1975, and contains accounts from soldiers and civilians, profiles of those involved, and a look at the role of women on the battlefield.